ANALISIS KONSEP WASATHIYYAH DALAM ISLAM OLEH ULAMA-ULAMA AL-AZHAR: KAJIAN HERMENEUTIKA - Muhammad Ridha (JUTEQ: JURNAL TEOLOGI & TAFSIR, 2025)
Wasathiyyah is a central concept in Islamic teachings, reflecting the values of balance, justice, and moderation in all aspects of life. This study aims to explore the understanding of Wasathiyyah from the perspective of Al-Azhar scholars through a hermeneutical approach. The research method used is library research with a qualitative approach and philosophical hermeneutic analysis of the works of scholars such as Dr. Muhammad al-Madani, Dr. Ali Muhammad Shalabiy, and Dr. Nour ad-Din Mukhtar al-Khadimiy. The findings show that Wasathiyyah is not merely a middle position, but a principle of divine justice rooted in the Qur’an and Hadith. Al-Azhar scholars apply contextual interpretations blended with universal values to keep Islam relevant and inclusive amid contemporary challenges. This study affirms the importance of hermeneutics in grounding the values of religious moderation so that Muslims can act justly, tolerantly, and with balance in their socio-religious life.